Economic Analysis of Sweet Orange in Sindhuli District of Nepal - Parajulee, Dipika; Kandel, Apekshya; Panta, Sangam; Devkota, Kedar (International Journal of Social Sciences and Management, 2021)
Sweet orange is one of the major fruit grown in mid-hills of Nepal. It ranks 2nd among the citrus fruits in terms of area and production after mandarin. The study depicts the socio economic aspect of sweet orange production in Sindhuli district.Data were collected from 60 randomly selected sweet orange growers from Tinkanya and Baseswor of Golanjor rural municipality using semi-structured interview schedule. Two FGD’s was done in those places for the triangulation of household survey.Analysis was done using SPSS and excel. Socio demographic studies revealed that majorly (93.3%), of growers were engaged in sweet orange farming. Most of the growers (98.3%) had agriculture as their major occupation. The average land holdings of the farmers was 0.53 ha in which 0.37 ha of land was occupied for sweet orange cultivation. The average sweet orange production of total sixty households was calculated to be 1981.83 kg/ha. The total cost of Rs. 25797.36/ha was estimated and the gross return from the production was Rs.72634/ha; the benefit cost ratio was found to be 2.81 which supports that sweet orange production is being a profitable farming business. Furthermore, insects attack followed by irrigation problems and difficulty in transportation followed by lack of market price information were the major problems found in the production and marketing of sweet orange respectively. There is a high potentiality of increasing the fruit productivity if the constraints against the sweet orange cultivation are addressed properly and adequately. Int. J. Soc. Sc. Manage. Vol. 8, Issue-3: 396-400